Introduction to Sociology - Cushion, Michael (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
COURSE OBJECTIVES:•Develop an ability to think sociologically•Gain a basic knowledge of the major issues of society•Increase your ability to think conceptually (i.e., using concepts to understand social phenomena)•Some additional skill-building goals:writing, reading, data gathering and analysis